CHARACTERISTIC PERFORMANCES OF THE MAIN FOUR PIG FARMING SYSTEMS IN MANOKWARI, WEST PAPUA - D. A. Iyai (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2012)
This research aimed to investigate opportunities for improving pig farming systems both in urban and rural areas of Manokwari, Papua Barat province-Indonesia. The research started by assessing the perspectives and perceptions of farmers in group meetings. A number of 386 pigs in cummulative was weighing and measured for life body weights and body condition scores. Papuan pig farmers were represented by Jayapura, Biak, Ambai and Ansus(Serui), Mee(Nabire), Arfak(Manokwari)and Ayamaru(Sorong)tribes. Non-Papuan pig farmers identified with ethnic groups of Batak, Toraja, Manado and Flores. The highest numbers of pigs kept were by semi-penned pig farmers, followed by pen and restrained pig farmers. About two hours per day was devoted to work in the restrained, semi-penned and pen pig keeping systems, while less than 1.5 hours per day was allocated by free-range pig farmers. In urban areas, feeding sources were kitchen and restaurant waste, and likewise crops and agriculture residues were in rural areas. Supplements and concentrates were used on a limited scale. Agricultural residues used were cassava, banana, taro, corn, grain and vegetable wastes. Litter sizes in the four pig farming systems were in average of 6 piglets/farrow/sow. Body condition scores were higher in pen pig keeping, i.e. 2.9 to 3, followed by semi-pen pigs, i.e. 2.1 to 3, free-range pigs, 2.1-2.8 and restrained pigs, i.e. 1.8 and 2.5 at different age levels. Economical and social quantitatives need further studies.